Modeling Distribution of Jobs Using Production Function - Anton Abdulbasah Kamil (STATISTIKA: Forum Teori dan Aplikasi Statistika, 2009)
This paper presents a theory in which the composition of jobs is always sub-optimal, we use a searchframework which is a natural tool to model a situation in which identical workers can end up indifferent jobs with very different compensation patterns. First we will show that if different types ofjobs have different creation (capital) costs, then those which cost more to create will have to payhigher wages due to rent sharing; therefore. There will naturally exist good and bad jobs in thiseconomy. Second, establish that in an unregulated market, the composition of jobs is in efficientlybiased towards bad jobs.